Complementary interference method for determining optical parameters of liquid crystals. (2nd April 2016) - Kowiorski, K.; Kędzierski, J.; Raszewski, Z.; Kojdecki, M.A.; Chojnowska, O.; Garbat, K.; Miszczyk, E.; Piecek, W.
ABSTRACT: Wedge cells of small apex angle, filled with liquid crystals, were used to determining optical characteristics as functions of temperature for three liquid crystalline mixtures recently produced and a reference nematic. The interference fringes appearing in polarised monochromatic light (of sodium yellow line) normally incident on the cell were exploited to measure the ordinary and extraordinary refractive indices in the reflection mode and birefringence in the transmission mode. The measurements were repeated using Abbe's refractometer for 6CHBT as the reference to verifying the precision. Additionally the order parameter was computed from birefringence as a function of temperature. The results confirm the usefulness of the method and provide the properties of two nematic liquid crystals of small and large birefringence and one smectic liquid crystal of medium birefringence, recently produced. The experimental systems served also to investigating phase transition between the liquid crystals and the isotropic liquid at near-clearing temperature.